Correction: Weak backbone CH⋯OC and side chain tBu⋯tBu London interactions help promote helix folding of achiral NtBu peptoids. Issue 39 (6th April 2016) - Angelici, G.; Bhattacharjee, N.; Roy, O.; Faure, S.; Didierjean, C.; Jouffret, L.; Jolibois, F.; Perrin, L.; Taillefumier, C.
Abstract : Correction for 'Weak backbone CH⋯OC and side chain t Bu⋯ t Bu London interactions help promote helix folding of achiral N t Bu peptoids' by G. Angelici et al., Chem. Commun., 2016, 52, 4573–4576.